Extraction and Determination of Total Phenolic and Flavonoid in Kapok Leaves (Ceiba pentandra L.) using Ethanol as Solvent - Dewi Nofita; Renatalia Fika; Neri Fadjria; Arfiandi Arfiandi (Chimica et Natura Acta, 2023)
Kapok (Ceiba pentandra L.) is traditionally used in medicine. Based on the phytochemical screening, the leaves contain phenolic compounds, including flavonoids and tannins. The method used to determine the total phenol content was the Folin-Ciocalteu method using gallic acid as standard solution. The linear regression equation obtained on measured at 765 nm is y = 0.0054x + 0.0272 with determination (r) and correlation coefficient (R2 ) of 0.9994 and 0.9997. Total phenolic content in ethanol extracts is 89.185 µg/ml calculated as gallic acid. Meanwhile, determination of flavonoid content used comparison standard of quercetin used the AlCl3 method. Measuring at a wavelength of 510 nm gives a linear regression equation y= 0.122 + 0.003x with r = 0.9984 and R2 = 0.9960. Flavonoid content in kapok leaves is 1.6287% w/w calculated as quercetin.